Fault Tolerant Control of Grid Connected Inverters Based on Low-Voltage Ride Through - Wang, Zaisheng; Zhao, Shiya; Li , Yang; Yang, Fang; Zhao, Zhan (International Journal of Mechanical and Electrical Engineering, 2024)
To enhance the reliability of new energy grid connected systems, a fault-tolerant model predictive control strategy with low-voltage ride-through capability for grid connected inverter bridge arms has been proposed. Firstly, the operational principles following a single-phase bridge arm fault in the grid-tied inverter are analyzed. Then, a fault-tolerant structure for the grid connected inverter is established by creating a virtual bridge arm using direct current-side capacitors. Subsequently, a current prediction model is established, and control is implemented using redundant vectors. Additionally, by dynamically adjusting reactive current compensation commands based on the relationship between grid voltage drops and reactive current commands, the system is ensured to maintain continuous and stable operation even during grid voltage fluctuations. Finally, experimental results demonstrate that this fault-tolerant control strategy can still maintain the continuous and stable operation of the system when bridge arm faults occur due to grid voltage drops at the inverter grid connection point.